Diagnosis dan diagnosis banding demensia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Indonesian tend towards ageing population, in which increase aging. Although aging not dementia similarity, but, how ever, its can accelerate proportion of dementia. Dementia has its highest rate in the population over age 75, the age group that is increasing it's a higher rate than any other. Dementia is a clinical state, diagnosable only by clinical methodes. It is important to distinguish the early stages of dementia, the clinical behavioral state from the non progressive changes known to occur in otherwise normal aging. An important goal in clinical evaluation of patient with suspected dementia is to find the cause. The approach to diagnosis in patient with dementia, comprises history, general physical examination, neurological examination, mental status examination and laboratory investigations (chemical , biological, imaging). Dementia can be caused by a multitude of different dementing deseases, some of which are arrestable or reversible and many of which are preventable. Because large gaps still exist in current knowledge on diagnosis of dementia, there are some specific recommendations for further research thatwill result in improving the defferential diagnosis ofdementing disease.